Model Kepemimpinan Autentik pada Sekolah Berbasis Agama Katolik - Paulus Eddy Suhartanto (Jurnal Psikologi Teori dan Terapan, 2022)
Authentic leadership research related to antecedents and consequences is still limited, especially with regard to antecedents and consequences. Several studies show that the role of psychological capital, self knowledge and self consistency has not been consistent. Likewise, related to organizational commitment as a consequence of authentic leadership. This study aims to examine the antecedent model and consequences of authentic leadership in Catholicism-based schools. Authentic leadership antecedent test involves those consisting of self knowledge, self consistency and psychological capital as antecedents to authentic leadership. Consequence testing involves organizational commitment. The results show that psychological capital has a greater correlation than self consistency and self knowledge. The implications of antecedent roles for authentic leadership and affective commitment need to be considered in the development of authentic leadership.